Environmental Impacts of a Solar Dish Coupled With a Micro-Gas Turbine for Power Generation - Agostini, A.; Carbone, C.; Lanchi, M.; Miliozzi, A.; Misceo, M.; Russo, V. (Frontiers in Energy Research, 2021)
Concentrated solar power (CSP) systems are regarded as a renewable energy source technology that can contribute to decoupling the energy mix from fossil fuel combustion and related environmental impacts. However, current small-scale CSP technologies (e.g., Dish-Stirling) have not entered the market yet due to high costs, complexity, and poor reliability. The EU-funded OMSoP (Optimised Microturbine Solar Power) project aimed at solving the small-scale CSP shortcomings by coupling a solar dish with the consolidated and relatively cheap technology of the micro gas turbine (MGT). In this study, an environmental life cycle assessment analysis of the production and operation of a CSP-MGT system is performed following an eco-design approach, thus identifying the environmental hotspots and how the system can be improved in terms of environmental impacts. The results of the analysis, per unit of electricity produced, were compared to other renewable technologies with the same level of dispatchability to better evaluate strengths and weaknesses of the system under exam. With regard to climate change, the greenhouse gas (GHG) emissions of the CSP-MGT system resulted in the same range as those generated by photovoltaic systems. However, the system can substantially be optimized and the GHG emissions per kWh can be reduced up to 73% with respect to the built prototype. The GHG emissions are much lower than the current Italian energy mix (by up to 94%). To reduce the environmental burden of CSP-MGT plants, the system design here considered should be revised by improving the component’s performance and significantly reducing the reflective surface and therefore the structural materials for the dish foundation and frame. The replacement of steel in the dish frame with aluminum increases all the environmental impact parameters and primary energy demand (17%–27% depending on the environmental category considered) but slightly reduces abiotic element depletion (by 9%).